ANALISIS ABSOLUTE NEUTROPHIL COUNT DI PASIEN KANKER PAYUDARA DENGAN KEMOTERAPI (Analysis of Absolute Neutrophil Count in Breast Cancer Patients with Chemotherapy) - Arifa Moidady; Tenri Esa; Uleng Bahrun (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
The Absolute Neutrophil Count (ANC) is the absolute number of neutrophil derived from the multiplication of the relative number ofleukocytes to the total neutrophil count. Neutrophils can be disturbed due to myelosupressive effects of chemotherapy. Fever is a commonsymptom in neutropenia patients due to chemotherapy. This fever is an emergency requiring rapid handling of Oncology and needsadministration of appropriate antibiotics. Therefore, the data on the occurence of neutropenia and its related fever in patients whomaccept chemotherapy after breast cancer it is important to be noted. This study is carried on to know the Absolute Neutrophil Count(ANC) in breast cancer patients with chemotherapy by analyzing them. The study was performed retrospectively by taking medical recorddata from January up to December 2012 in Dr. Wahidin Sudirohusodo Hospital Makassar. The absolute Neutrophil Count pre and afterchemotherapy analysis was done to determine neutropenia, as well as the febrile neutropenia and the correlation between ANC withpatients age and stage of breast cancer. A total of 55 samples with the majority of patients (85.45%) were in the age group of 41–60years old. The ANC after chemotherapy occurred in 50 patients were decreased (90.91%). There are five (5) patients (9.09%) with feverand two (2) persons (patients) (3.63%) suffered febrile neutropenia. The correlation analysis between decreased ANC with patient ageand stage of breast cancer are p=0.054 and 0.070 respectively. Based on this study it can be concluded, that decreased ANC occurredin most patients after accepting chemotherapy but only few patients suffered febrile neutropenia. There was no significant correlationbetween the decreased ANC with patient age and stage of breast cancer.